Efeitos da interação e da movimentação de parasitoides especialista e generalista no controle da broca da cana - Macedo, Allan Mello de (2022)
The dependence of parasitoids on hosts for reproduction, and the fact of their foraging behavior and reproductive success be strictly related to their hosts, making them important agents in biological pest control programs. However, the release of parasitoids and their movement in crop areas can lead to the establishment of complex interactions of these with the community of herbivores and natural enemies present in the agricultural landscape. In this context, unpredictable results can occur when generalist and specialist parasitoid species compete for a common host, the target pest to be controlled. The frequency and abundance of alternative hosts of generalist parasitoids play an important role in modulating the competition with specialist parasitoids, defining the balance between costs and benefits arising from the switching of hosts when it chooses to attack a common host, directly affecting the success of biological control. Through mathematical modeling, this study aimed to analyze the effects of competition between specialist and generalist parasitoids for Diatraea saccharalis, the sugarcane borer. For this, biological parameters obtained from interaction among Cotesia flavipes, specialist parasitoid, Tetrastichus howardi, generalist parasitoid species, and D. saccharalis were used, aiming to answer the following questions: (i) Is the associate release of specialist and generalist parasitoid species effective for the pest control? (ii) Does the parasitoid release site in the crop area influence species’ effectiveness of pest control? (iii) Considering the costs of host switching and interspecific competition interaction, what is the effect of the alternative host variations on making parasitism to a common host advantageous for the generalist parasitoid population and consequently for its use in biological control programs? (iv) Do the location of the target host (i.e., pest) and alternative hosts in the agricultural landscape interfere with the generalist parasitoid’s permanence in the target crop and, consequently, with the biological control effectiveness?